The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1108/17556221111171711
|View full text |Cite
|
Sign up to set email alerts
|

Teaching ideas for generating critical and constructive insights into well‐functioning multidisciplinary mental health teams

Abstract: PurposeIt is now common place for mental health services to operate using multidisciplinary teams (MDTs) where several health professionals simultaneously maintain their disciplinary distinctiveness and assume complementary professional roles. This requires awareness of other team members' disciplines and good team‐work skills. Yet in Australia, the preparation of health professionals continues to occur primarily in single‐discipline programs, where interaction with other disciplines often only occurs in an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Mental health care is commonly delivered by a team consisting of different clinical disciplines, including: nursing; psychiatry; psychotherapy; psychology; social work; occupational therapy; and other branches of general or specific health disciplines [5] [6].…”
Section: Main Text Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental health care is commonly delivered by a team consisting of different clinical disciplines, including: nursing; psychiatry; psychotherapy; psychology; social work; occupational therapy; and other branches of general or specific health disciplines [5] [6].…”
Section: Main Text Introductionmentioning
confidence: 99%
“…For future health professionals, typical clinical placements are not often conducive to highlighting the importance of multidisciplinary mental health care to individualized care and recovery. McAllister et al [6] contend that 'the preparation of health professionals occurs primarily in single-discipline programs, where interaction with other disciplines often only occurs in an ad hoc, time-limited way. ' Mann et al [10] explain that a fully integrated educational experience, which involves a number of health disciplines in joint learning experiences, is what is needed to effectively prepare health professionals to work collaboratively in health care teams.…”
Section: Main Text Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, successful MDTs play an important role in the education, training, and ultimately recruitment of new staff to desperately needy rural and remote areas. While barriers and challenges to cross-disciplinary learning exist, there are many benefits of integrated and multidisciplinary mental health service learning models that may be attributed to their patient focus as well as to their adaptation to case complexity (Morrissey et al 2011;McAllister et al 2011). Integrating and sharing learning across disciplines provide cross-fertilization of skills and experience across services and regions.…”
Section: Establishing Multidisciplinary Teamsmentioning
confidence: 99%
“…A recently developed "Learning Package" (LP) for providing IPE for nursing, psychology and occupational students prior to their engaging in practical placements (Morrissey et al, 2010) was funded by the Australian Learning and Teaching Council (ALTC) and evaluated with three groups of students at two Australian universities. Outcomes showed that the LP enhanced interprofessional knowledge, and improved understanding and communication skills across professions (McAllister et al, 2011).…”
mentioning
confidence: 99%